Japan’s Defense Strategy Transformation in the Indo-Pacific: Relevance, Opportunities, and Challenges for Indonesia’s Defense Diplomacy - Ita Nurjanah; Fauzia Gustarina Cempaka Timur; Frega Wenas Inkiriwang (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Japan’s defense diplomacy in the Indo-Pacific has received increasing scholarly attention, particularly in relation to the evolution of the Free and Open Indo-Pacific (FOIP) strategy and regional security dynamics. However, studies specifically examining the transformation of Japan’s defense diplomacy from FOIP 1.0 to FOIP 3.0 and its strategic implications for Indonesia remain limited. This study aims to analyze the transformation of Japan’s defense diplomacy in the Indo-Pacific and assess its strategic implications for Indonesia. Employing a qualitative case study design, this research examines Japan’s evolving defense diplomacy architecture in the Indo-Pacific region. Data were collected through document analysis of official government documents, defense white papers, policy reports, and relevant academic literature, and were analyzed using thematic and content analysis techniques. The findings indicate that Japan’s defense diplomacy has shifted from a traditionally reactive security posture toward a more proactive, multidomain, and technology-oriented strategy encompassing maritime security, cybersecurity, space cooperation, alliance interoperability, and Official Security Assistance (OSA). The findings further show that Japan increasingly functions as a proactive security provider through multidomain cooperation and institutionalized defense diplomacy mechanisms. This study contributes to the development of Neoclassical Realism and defense diplomacy literature by demonstrating how states adapt to systemic pressures through non-coercive security instruments and multidomain engagement. The conclusion emphasizes the importance of balanced and adaptive defense diplomacy for Indonesia in strengthening maritime security, cybersecurity, and strategic autonomy amid intensifying Indo-Pacific geopolitical competition. The study offers practical implications for policymakers in designing adaptive and balanced defense cooperation strategies and provides opportunities for further comparative research on defense diplomacy among Indo-Pacific middle powers.